1994
DOI: 10.1093/infdis/170.5.1279
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Increases In Load Of Human Immunodeficiency Virus Correlate With Early Disease Progression and Loss of CD4 Cells in Vertically Infected Infants

Abstract: The relationship between viral burden, timing of transmission, and clinical progression was investigated in 110 children at risk for vertical human immunodeficiency virus (HIV) infection using quantitative polymerase chain reaction, coculture, and immune complex-dissociated p24 antigen assay. In a cross-sectional study, the mean HIV DNA copy number in 19 symptomatic children was significantly higher than in 31 infected, asymptomatic children (420 +/- 125 vs. 87 +/- 78; P < .0001). In a second group of 8 vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 11 publications
3
34
2
2
Order By: Relevance
“…A rapid increase in viral load, as assessed by the HIV-1 DNA copy number, was found to be strictly associated with the early onset of symptoms; conversely, infants with slower disease progression showed a very gradual increase in the proviral DNA content (12). By studying a larger number of samples obtained early in life, and using a sensitive cRT-PCR technique to determine the HIV-1 RNA content in plasma, we were also able to identify transient increases in plasma viremia, and delineate a more complex pattern of HIV-1 replication in the slow progressors.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A rapid increase in viral load, as assessed by the HIV-1 DNA copy number, was found to be strictly associated with the early onset of symptoms; conversely, infants with slower disease progression showed a very gradual increase in the proviral DNA content (12). By studying a larger number of samples obtained early in life, and using a sensitive cRT-PCR technique to determine the HIV-1 RNA content in plasma, we were also able to identify transient increases in plasma viremia, and delineate a more complex pattern of HIV-1 replication in the slow progressors.…”
Section: Discussionmentioning
confidence: 93%
“…Although the precise timing of vertical transmission cannot be pinpointed, the above findings suggest that HIV-1 replicates and spreads to the peripheral blood cells mainly after birth. Moreover, recent observations indicating that a rapid increase of HIV-1 DNA in cells during the first weeks of life is correlated with a rapid onset of disease (11,12) support a relationship between the HIV-1 replication pattern early in life and the clinical outcome, and stress the need to elucidate the dynamics of HIV-1 activity soon after birth for further comprehension of pediatric AIDS.…”
Section: Introductionmentioning
confidence: 96%
“…Patients were categorized as CR if they had suppression of plasma HIV RNA levels <400 copies=ml, as measured by Amplicor standard HIV-1 Monitor Test and <50 copies=ml by the ultrasensitive Amplicor HIV-1 Monitor Ò Test, v1.5 when available (Roche Molecular Diagnostics, Indianapolis, IN). 18 Plasma samples from the infants and children were used for neutralization of their autologous viral isolates over time. We selected five subjects for evaluation of sequential ANAB titers on the basis of available paired plasma samples and viral isolates.…”
Section: Patientsmentioning
confidence: 99%
“…Members of the TNFR super family could mediate pleiotropic biological processes, such as cell proliferation, differentiation, apoptosis and cytokine production [4][5][6][7][8][9]. Several other studies had shown a significant increase of Fas receptors and ligand levels in plasma or serum of HIV-1 infected individuals, compared to their negative control subjects [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%